Combined effects of soil silicon and host plant resistance on planthoppers, blast and bacterial blight in tropical rice - Vu, Quynh; Dossa, Gerbert Sylvestre; Mundaca, Enrique A.; Settele, Josef; Crisol-Martínez, Eduardo; Horgan, Finbarr G. (MDPI, 2022)
Soil silicon enhances rice defenses against a range of biotic stresses. However, the magnitude of these effects can depend on the nature of the rice variety. We conducted a series of greenhouse experiments to examine the effects of silicon on planthoppers (Nilaparvata lugens [BPH] and Sogatella furcifera [WBPH]), a leafhopper (Nephotettix virescens [GLH]), blast disease (Magnaporthe grisea) and bacterial blight (Xanthomonas oryzae) in susceptible and resistant rice. We added powdered silica gel (SiO2) to paddy soil at equivalent to 0.25, 1.0, and 4.0 t ha−1. Added silicon reduced BPH nymph settling, but the effect was negligible under high nitrogen. In a choice experiment, BPH egg-laying was lower than untreated controls under all silicon treatments regardless of nitrogen or variety, whereas, in a no-choice experiment, silicon reduced egg-laying on the susceptible but not the resistant (BPH32 gene) variety. Stronger effects in choice experiments suggest that silicon mainly enhanced antixenosis defenses. We found no effects of silicon on WBPH or GLH. Silicon reduced blast damage to susceptible and resistant (Piz, Piz-5 and Pi9 genes) rice. Silicon reduced damage from a virulent strain of bacterial blight but had little effect on a less virulent strain in susceptible and resistant (Xa4, Xa7 and Xa4 + Xa7 genes) varieties. When combined with resistance, silicon had an additive effect in reducing biomass losses to plants infested with bacterial blight (resistance up to 50%; silicon 20%). We discuss how silicon-containing soil amendments can be combined with host resistance to reduce biotic stresses in rice.